2018
DOI: 10.1002/cncr.31755
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin for recurrent Hodgkin lymphoma after allogeneic hematopoietic stem cell transplantation: A report from the EBMT Lymphoma Working Party

Abstract: BACKGROUND:The treatment of patients with Hodgkin lymphoma (HL) who develop disease progression after undergoing allogeneic stem cell transplantation (allo-SCT) remains challenging. METHODS: The authors assessed outcomes in 184 adult patients with HL who developed disease recurrence or progression after a matched related or unrelated allo-SCT at European Society for Blood and Marrow Transplantation-participating centers between 2010 and 2014. RESULTS: Eighty patients who received brentuximab vedotin (BV) salva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…CD30 blockade compromises the CD4+ T-cell mediated immune system ( 18 ). A recent report suggested that brentuximab with/without DLI is an effective salvage therapy for relapse of HL after alloHCT irrespective of pretransplant use of brentuximab ( 19 ). We described an HL patient who relapsed after alloHCT and in whom PR was achieved after three cycles of brentuximab and DLI.…”
Section: Discussionmentioning
confidence: 99%
“…CD30 blockade compromises the CD4+ T-cell mediated immune system ( 18 ). A recent report suggested that brentuximab with/without DLI is an effective salvage therapy for relapse of HL after alloHCT irrespective of pretransplant use of brentuximab ( 19 ). We described an HL patient who relapsed after alloHCT and in whom PR was achieved after three cycles of brentuximab and DLI.…”
Section: Discussionmentioning
confidence: 99%
“…At last follow-up, 34% of the original BV cohort were alive and in CR versus 18% in the group that did not receive BV (p = 0.003). The combination of BV with donor lymphocyte infusion was associated with the highest probability of being alive in CR at the time of last follow-up [68].…”
Section: Immunotherapies For Relapse After Allogeneic Hctmentioning
confidence: 92%
“…The probability of being alive and in CR was highest in the group of patients who received BV followed by DLI (40%) compared to 11% in patients who did not receive any, 24% in patients who received DLI only, 21% in patients who received BV only, and 24% in patients who received DLI followed by BV (p = 0.003). In multivariate analysis, the use of DLI was found to significantly improved OS [HR 0.51 (0.32-0.83), p = 0.007] [68]. There are two main studies assessing the use of CPI after allo-HCT.…”
Section: Immunotherapies For Relapse After Allogeneic Hctmentioning
confidence: 99%
“…Post-transplantation BV may synergize with immune intervention such as DLI to achieve sustained control of HL recurring after allo-HCT. Prospective randomized trials are needed to address this question [69].…”
Section: Haploidentical Stem-cell Transplantationmentioning
confidence: 99%